Extreme star formation modes in interacting dwarf galaxies - García del Valle Espinosa, María de la Macarena (The University of Edinburgh, 2025)
In the Local Universe, the vast majority of dwarf galaxies (M < 10⁹M⊙) are either satellites of a more massive host, or isolated. Dwarf pairs are exceedingly rare, being less than 5% among the low-mass systems. While infrequent at z = 0, the hierarchical nature of galaxy formation implies dwarf-dwarf interactions to be very common at early times. Therefore, interacting dwarf galaxies in the nearby Universe open a unique window to the star formation processes that operate at early epochs, as they resemble the physical conditions of primordial galaxies, but with a detail and sensitivity unmatched by high redshift observations. In this thesis, I aim to advance our understanding of the star formation processes that operate in the early Universe. To do that, I carry out a detailed multiwavelength study of a nearby (Dₗ =23Mpc) interacting dwarf galaxy pair, namely UGC 5205 and CGCG007-025. The strong interaction has triggered nearly coeval galaxy-scale starbursts, with a delay time of approximately 500 Myr between them. It has also altered their stellar structure and content, as indicated by the presence of prominent tidal features. Using broadband photometry from the Wide Field Camera 3 at Hubble Space Telescope (WFC3/HST) and integral field spectroscopy from the Multi Unit Spectroscopic Explorer at the Very Large Telescope (MUSE/VLT), I characterise the stellar populations and ionised gas properties of these systems and discuss their resemblance with early star formation. The more massive companion, UGC 5205, is a post-starburst dwarf with an extended tidal tail. The interaction-induced high pressure of the starforming event has created a large population of young massive clusters (YMCs). In the first chapter, I catalogue the YMCs and estimate their physical properties –such as mass and age– using SED fitting. Then, I derive the cluster mass function as a function of the galaxy environment, finding evidence that the truncation mass is not universal. Exploiting MUSE data, I study the properties of the host galaxy, namely the star formation history (SFH) and the total stellar mass formed in the last burst. Finally, I compare this total mass to the mass enclosed in the clusters and calculate the cluster formation efficiency, Γ. A value of Γ ≈ 15% suggests the YMCs population in UGC 5205 has not experienced significant disruption events. In the second chapter of the thesis I study the less massive companion, CGCG 007-025. This galaxy features a strong off-centre starburst with giant, metal-poor Hii regions. However, the MUSE data reveals an underlying old stellar population. The SFH is compatible with a long quiescent period until very recently, with the newest starbursting episode being 5 Myr old, dated by the presence of Wolf-Rayet stars. Opposite to the other galaxy, the star-forming event has not been efficient enough to form bounded star clusters. Furthermore, the optical spectrum of this galaxy is predominantly composed of strong emission lines. Using the emission line fluxes, I derive the physical properties of the ionised gas and the star formation rate (SFR) surface density, which displays a clumpy distribution. Together with photoionisation modelling, I estimate the gas-phase metallicity, that shows an anti-correlation with the SFR surface density. All together, this suggests the accretion of pristine gas is responsible for the rejuvenation of the galaxy, likely fostered by the interaction. In the last chapter, I further investigate the complex structure of the emission line profiles in the brightest star-forming region of CGCG 007- 025. To do so, I acquired high-resolution echelle spectroscopy using Magellan/MIKE, whose wide wavelength coverage permits a detailed chemodynamical study of the region. Using the fluxes of 30 emission lines simultaneously, I derive the electron temperature, Te, electron density, ne, and chemical abundances using the direct method. The high spectral resolution (R∼40,000) allows us to resolve kinematic components not visible in previous datasets. Together with the detection of the He ii emission line, I found evidence of shocks superimposed with stellar photoionisation as the main ionising mechanisms of this starbursting region. In summary, this thesis aims to investigate the star-forming processes that operate at high redshift by studying the resolved physical and chemical properties of a pair of local dwarf galaxies in interaction. The interaction has led to star forming episodes on galactic scales in both galaxies, favouring the formation of massive stellar clusters. Similar environments at high redshift could be the mechanisms which explain the origin of the globular cluster we see now.
Keywords: Interacting Dwarf Galaxies; Star Formation; Young Massive Clusters (YMCs); Tidal Features; Galaxy Interaction